Sustainable Architecture as a Concept of Rationalizing Consumption ‏and Improving the Environment - Haitham Ibrahim Elhadidy; Sarah Fahmy (Journal of Architecture, Art & Humanistic Science, 2020)
The interest in the environment and its problems increased as adversely affects current and ‎future generations, especially with regard to the energy field, which prompted the world to ‎search for solutions to eliminate these problems and find common values between sustainable ‎development and energy. Based on reconciling the concepts of development, energy ‎rationalization, and a green environment to reach environmental sustainability.‎‎ The pioneers of sustainability in environmental architecture, and many academic and ‎professional organizations, have worked hard on developing the means of achieving ‎sustainability and applying them to modern buildings, leading to the concept of sustainable ‎architecture.‎‎ This has led to the development of a societal view towards the internal and external ‎environment of Egyptian homes from being architectural facilities for housing only. In order to ‎develop them into entities with environmental, economic and social responsibility. All of this ‎requires a deeper development of the role of studies towards identifying elements for ‎improving the environment from the design, economic and social side for energy-efficient ‎buildings.‎‎ The interaction of human beings with the environmental components has led to the depletion ‎of their natural resources. In view of the tremendous development in information technology ‎and the changing concepts of space, time and human relations. Therefore it has become ‎necessary to develop the concepts of architecture in accordance with the expected future ‎changes, as happened in the era of modernity and the period of postmodernism leading to ‎superior modernity, and future thinking in Sustainable environmental designs.‎‎ By applying the concepts of sustainable architecture through design practices in the building ‎industry, it cannot be possible made by qualified designers in this field, which will lead to ‎finding appropriate solutions to environmental, economic and functional problems. The ‎concept of environmental design linked to exploiting the components of the natural and ‎geographical environment to obtain the necessary energy, to provide a comfortable ‎environment for housing, while protecting the environment, preserving its natural properties, ‎and resorting to new sources of energy.‎‎ The traditional residence is a good example of applying sustainable design concepts in terms ‎of design principle, building materials and environmental treatments, as it relied on exploiting ‎natural energy sources such as sun, wind, topography of the site, to provide a comfortable ‎interior environment, and to align it with social values and customs and traditions of society.‎